Nonlinear bending behavior of a multilayer copper conductor in a dynamic power cable. (15th April 2022) - Hu, Haitao; Yan, Jun; Sævik, Svein; Ye, Naiquan; Lu, Qingzhen; Bu, Yufeng
Abstract: Reciprocating bending behavior is the main factor leading to the fatigue failure of dynamic power cables. However, in the research on the reciprocating bending behavior of dynamic cables, only the mechanical properties of the armored steel wire has been considered thus far and the copper conductor is disregarded. In this paper, the nonlinear bending properties of multilayer helically wound copper conductors are studied by experiments and numerical simulation. The research can provide accurate data of nonlinear bending mechanical properties of copper conductor for hydrodynamic analysis of dynamic cable fatigue life. Firstly, the nonlinear bending hysteresis curves of copper conductors are obtained by a reciprocating bending experiment of copper conductor. Secondly three-dimensional finite element numerical simulations of the copper conductor's bending behavior were also conducted. The numerical results from the finite element model were compared with the experimental data. Finally, sensitivity analysis of the structural parameters of the copper conductor was performed. The research shows that copper conductor has obvious nonlinear bending hysteresis behavior. The change of friction coefficient and radial extrusion pressure from the conductor's outer sheath layer have obvious effects on the critical sliding curvature and bending hysteresis properties of nonlinear bending properties of copper conductors. Highlights: The bending hysteresis behavior of a multilayer helically wound copper conductor in a dynamic power cable is studied. The bending hysteresis curve of a copper conductor is obtained by prototype tests. A 3D finite element model is established to study the bending hysteretic behavior of the copper conductor. The influence of friction coefficients between copper wires and between copper wire and outer sheath layer on the bending hysteretic behavior is discussed. The influence of the radial extrusion pressure on the bending hysteretic behavior is discussed.